EFFECTS OF STROBILANTHES CRISPUS EXTRACT ON THE APOPTOTIC PATHWAY OF HUMAN LIVER CARCINOMA CELL LINES - Endrini, Susi; Suherman, Suherman; Rahmat, Asmah; Ismail, Patimah; Taufiq-Yap, Y.H; Othman, Fauziah (Jurnal Kedokteran YARSI, 2007)
Previous study has been shown the potential anticarcinogenic effect of Strobilanthes crispus, a plant native to countries from Madagascar to Indonesia, on human liver cancer (HepG-2) cell lines. The objective of the present study was to investigate the mechanism of anticarcinogenic effectof S.crispus extract through apoptotic pathway. Exposure of HepG-2 cells to S.crispus extract resulted in induction of apoptosis in a dose-dependent manner as measured by Fluoresence Microscopy and Confocal Laser Scanning Microscopy analysis. These findings provide important new insight into the possible molecular mechanisms of the anticancer activity of S.crispus.